Wrinkling, fracture, and necking: The various failure modes in maritime crash: - Atli-Veltin, B.; Dekker, R.; Brunner, S.K.; Walters, C.L. (2016)
Depending on the state of stress, material can fait in a number of different modes during a collision. Three modes are identified here as material separation in the absence of necking, material separation after the onset of necking, and localized buckling/wrinkling. Through a series of case studies, the states of stress present in a collision are analyzed. Of particular interest is leakage in a scaled fuel tank that could not have been predicted by FEA due to resolution and may have been ignored even with sufficient resolution because it was in a region of generally compressive stresses. Following the review of case studies, the aforementioned failure mechanisms are reviewed, and the corresponding states of stress are summarized. It is shown that the current state of technology for failure after the onset of necking is insufficient but quickly improving. Concepts are taken from the sheet metal industry to understand the onset of buckling/wrinkling, but there is little readily available to simulate failure after the initial onset.